Increasing lipid production in Chlamydomonas reinhardtii through genetic introduction for the overexpression of glyceraldehyde-3-phosphate dehydrogenase - Shin, Sung-Eun; Koh, Hyun Gi; Park, Kyungmoon; Park, See-Hyoung; Chang, Yong Keun; Kang, Nam Kyu (Frontiers in Bioengineering and Biotechnology, 2024)
Microalgae, valued for their sustainability and CO 2 fixation capabilities, are emerging as promising sources of biofuels and high-value compounds. This study aimed to boost lipid production in Chlamydomonas reinhardtii by overexpressing chloroplast glyceraldehyde-3-phosphate dehydrogenase (GAPDH), a key enzyme in the Calvin cycle and glycolysis, under the control of a nitrogen-inducible NIT1 promoter, to positively impact overall carbon metabolism. The standout transformant, PNG#7, exhibited significantly increased lipid production under nitrogen starvation, with biomass rising by 44% and 76% on days 4 and 16, respectively. Fatty acid methyl ester (FAME) content in PNG#7 surged by 2.4-fold and 2.1-fold, notably surpassing the wild type (WT) in lipid productivity by 3.4 and 3.7 times on days 4 and 16, respectively.Transcriptome analysis revealed a tenfold increase in transgenic GAPDH expression and significant upregulation of genes involved in fatty acid and triacylglycerol synthesis, especially the gene encoding acyl-carrier protein gene (ACP, Cre13.g577100.t1.2). In contrast, genes related to cellulose synthesis were down-regulated. Single Nucleotide Polymorphism (SNP)/Indel analysis indicated substantial DNA modifications, which likely contributed to the observed extensive transcriptomic and phenotypic changes. These findings suggest that overexpressing chloroplast GAPDH, coupled with genetic modifications, effectively enhances lipid synthesis in C. reinhardtii. This study not only underscores the potential of chloroplast GAPDH overexpression in microalgal lipid synthesis but also highlights the expansive potential of metabolic engineering in microalgae for biofuel production.